Perilaku Pemilih Etnik Batak terhadap Pemilihan Kepala Daerah - Sari, Ika Ratna; Warjio, Warjio (Universitas Sumatera Utara, 2018)
This article discusses about the relationship of clan/ethnicity in choosing. Ethnic problems / clan similarities are a problem thatâs often debated in Indonesia